1982
DOI: 10.1620/tjem.138.309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irradiation on the pulmonary vascular fluid and protein exchange.

Abstract: In anesthetized sheep, ventilated by positive pressure, pulmonary arterial and left atrial pressures, cardiac output, and lung lymph flow (Qlym) were measured and lymph-to-plasma protein concentration ratio (L/P) was determined. Four sheep were irradiated with 60Co on the bilateral lower lobes, avoiding irradiation on the heart and the caudal mediastinal lymph node. Qlym increased during and after irradiation, and reached a new steady state (160% increase), while pulmonary arterial or left atrial pressure did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…We believe this reflects the coarse-fractionated dose regime and the relatively small volume targeted in the present study. Indeed it has previously been shown that sheep will develop radiation pneumonitis typical of that seen in humans given sufficient dose and lung volume targeted 37 41 . Unilateral single fraction high dose irradiation (30 Gy) of the sheep thorax produced radiation pneumonitis typical of the syndrome in humans at 4 weeks after irradiation 41 , and whole lung single fraction irradiation (15 Gy) of sheep resulted in the development of progressive dyspnoea three weeks after exposure; however animals were killed at 4 weeks precluding longer term assessment 38 .…”
Section: Discussionmentioning
confidence: 99%
“…We believe this reflects the coarse-fractionated dose regime and the relatively small volume targeted in the present study. Indeed it has previously been shown that sheep will develop radiation pneumonitis typical of that seen in humans given sufficient dose and lung volume targeted 37 41 . Unilateral single fraction high dose irradiation (30 Gy) of the sheep thorax produced radiation pneumonitis typical of the syndrome in humans at 4 weeks after irradiation 41 , and whole lung single fraction irradiation (15 Gy) of sheep resulted in the development of progressive dyspnoea three weeks after exposure; however animals were killed at 4 weeks precluding longer term assessment 38 .…”
Section: Discussionmentioning
confidence: 99%